Women and Islamic Law: Exploring Interpretative Authenticity and Gender Harmony within Qur’anic and Juristic Traditions - Nataliia Bodnar (International Journal of Sharia and Law, 2026)
Legal systems in multi-religious states often struggle to harmonize Islamic jurisprudence with constitutional equality norms, particularly in gender-sensitive disputes. Existing studies explore either internal hermeneutics of Usul al-Fiqh or external comparative frameworks, but seldom test how their integration affects real-world judgments. The article investigates whether coupling maqāṣid-centred interpretation with procedural adaptability can systematically advance gender-equitable outcomes across pluralistic jurisdictions. An explanatory sequential mixed-method design was applied to 129 appellate judgments, 38 statutes, and 53 qualitative interviews drawn from Indonesia, South Africa, and the United Kingdom. Two original metrics were developed: the Maqāṣid Alignment Index (MAI) measuring doctrinal fidelity to equality and welfare, and the Trans-Systemic Convergence Score (TCS) capturing procedural flexibility, statutory amenability, and outcome parity. Semantic-network analysis identified bridging concepts, while logistic regression estimated the predictive power of MAI and TCS for gender-equitable relief. Judgments situated in the highest MAI–TCS tercile granted equitable remedies in 78 % of cases, compared with 22 % in the lowest tercile. Each one-standard-deviation increase in MAI multiplied the odds of favorable relief by 8.5 (p < 0.001), and a comparable rise in TCS did so by 6.5 (p < 0.01). Network metrics revealed a small-world topology anchored by maṣlaḥa and constitutional equality clauses, highlighting doctrinal nodes where targeted reform can yield maximal systemic impact. Integrating maqāṣid-oriented hermeneutics with adaptive procedural tools provides an empirically validated pathway toward inclusive jurisprudence, offering legislators and jurists a replicable model for aligning Islamic legal reasoning with universal justice norms.